Level of Emotional Balance among Students with Learning Disabilities and its Relationship to Self-Acceptance - Ahmad Mohammad Melhem; Tahani Bassam Al-Shamayleh (دراسات: العلوم التربوية, 2022)
Objectives: This study aims to identify the level of emotional balance of students with LD and its relationship to self-acceptance.